Using 'allergy tests' in cases of canine dermatitis. Issue 3 (12th February 2019) - Foster, Aiden
Abstract : Veterinary clinicians and owners have access to a variety of commercial serological tests that purport to measure immunoglobulin (Ig) E, and in some situations IgG, antibodies to various allergens. However, there is considerable confusion about how to use these tests and a great potential for misusing them and for wasting clients' money. The aim of this article is to provide an overview of how these tests can be used to help the diagnosis and treatment of allergic skin conditions in dogs.